Detection of circulating tumor cells using manually performed immunocytochemistry (MICC) does not correlate with outcome in patients with early breast cancer – Results of the German SUCCESS-A- trial. Issue 1 (December 2016) - Jueckstock, Julia; Rack, Brigitte; Friedl, Thomas; Scholz, Christoph; Steidl, Julia; Trapp, Elisabeth; Tesch, Hans; Forstbauer, Helmut; Lorenz, Ralf; Rezai, Mahdi; Häberle, Lothar; Alunni-Fabbroni, Marianna; et al.
Abstract Background Recently, the prognostic significance of circulating tumor cells (CTCs) in primary breast cancer as assessed using the Food-and-Drug-Administration-approved CellSearch® system has been demonstrated. Here, we evaluated the prognostic relevance of CTCs, as determined using manually performed immunocytochemistry (MICC) in peripheral blood at primary diagnosis, in patients from the prospectively randomized multicenter SUCCESS-A trial (EudraCT2005000490-21). Methods We analyzed 23 ml of blood from 1221 patients with node-positive or high risk node-negative breast cancer before adjuvant taxane-based chemotherapy. Cells were separated using a density gradient followed by epithelial cell labeling with the anti-cytokeratin-antibody A45-B/B3, immunohistochemical staining with new fuchsin, and cytospin preparation. All cytospins were screened for CTCs, and the cutoff for positivity was at least one CTC. The prognostic value of CTCs with regard to disease-free survival (DFS), distant disease-free survival (DDFS), breast-cancer-specific survival (BCSS), and overall survival (OS) was assessed using both univariate analyses applying the Kaplan–Meier method and log-rank tests, and using multivariate Cox regressions adjusted for other predictive factors. Results In 20.6 % of all patients (n  = 251) a median of 1 (range, 1–256) CTC was detected, while 79.4 % of the patients (n  = 970) were negative for CTCs before adjuvant chemotherapy. A pT1 tumor was present in 40.0 % of patients, 4.8 % had G1 grading and 34.6 % were node-negative. There was no association between CTC positivity and tumor stage, nodal status, grading, histological type, hormone receptor status, Her2 status, menopausal status or treatment. Univariate survival analyses based on a median follow-up of 64 months revealed no significant differences between CTC-positive and CTC-negative patients with regard to DFS, DDFS, BCSS, or OS. This was confirmed by fully adjusted multivariate Cox regressions, showing that the presence of CTCs (yes/no) as assessed by MICC did not predict DFS, DDFS, BCSS or OS. Conclusions We could not demonstrate prognostic relevance regarding CTCs that were quantified using the MICC method at the time of primary diagnosis in our cohort of early breast cancer patients. Further studies are necessary to evaluate if the presence of CTCs assessed using MICC has prognostic relevance, or can be used for risk stratification and treatment monitoring in adjuvant breast cancer. Trial registration The ClinicalTrial.gov registration ID of this prospectively randomized trial isNCT02181101 ; the (retrospective) registration date was June 2014 (study start date September 2005).